2010
DOI: 10.1002/chem.200902336
|View full text |Cite
|
Sign up to set email alerts
|

Electron Donor–Acceptor Interactions in Regioselectively Synthesized exTTF2–C70(CF3)10 Dyads

Abstract: The decakis(trifluoromethyl)fullerene C(1)-C(70)(CF(3))(10), in which the CF(3) groups are arranged on a para(7)-meta-para ribbon of C(6)(CF(3))(2) edge-sharing hexagons, and which has now been prepared in quantities of hundreds of milligrams, was reacted under standard Bingel-Hirsch conditions with a bis-pi-extended tetrathiafulvalene (exTTF) malonate derivative to afford a single exTTF(2)-C(70)(CF(3))(10) regioisomer in 80 % yield based on consumed starting material. The highly soluble hybrid was thoroughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…This compound can be prepared with up to 90% purity (without HPLC separation) and with up to 55 mol % yield. 68 , 99 Using a gas handling system is used with an oil bubbler serving as a pressure release, and ambient pressure of CF 3 I is maintained during the synthesis (see ref ( 101 ) for the only example of a variable-pressure closed-loop flow tube reactor). Very long residence times can be achieved if a long hot zone and a slow CF 3 I flow rate are used.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This compound can be prepared with up to 90% purity (without HPLC separation) and with up to 55 mol % yield. 68 , 99 Using a gas handling system is used with an oil bubbler serving as a pressure release, and ambient pressure of CF 3 I is maintained during the synthesis (see ref ( 101 ) for the only example of a variable-pressure closed-loop flow tube reactor). Very long residence times can be achieved if a long hot zone and a slow CF 3 I flow rate are used.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Perfluoroalkylated fullerenes are typically prepared as mixtures of multiple isomers and multiple compositions. In a few cases, higher synthetic selectivity has been realized, but even in these cases a chromatographic separation was necessary to obtain 98+% pure PFAFs (for example, see the synthesis of 70-10-1 (T1#39,72) 68 , 99 and a synthesis of the series of compounds 60-2-1 R F (T1#111,114) 101 , 104 ). Except for a few early reports that used flash chromatography and gel permeation chromatography (T1#7,9,17 10 , 14 , 17 ), reverse-phase HPLC using specialized columns designed and optimized for fullerene separation has been employed.…”
Section: Physical Properties and Separation Methods Of Pfafsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product was analyzed by 1 H, 19 F, and 31 P NMR and MALDI mass spectrometry. Two peaks were present in the mass spectrum; 1830 m/z is 14 more than desired product and unknown, 1748 m/z is C 60 (CF 3 ) 9 (malonate/phosphonic ester) + 1, which corresponds to the loss of one CF 3 group in the mass spec experiment. Yield: 14.7 mg, 32% yield based on starting 60-10-3.…”
Section: Synthesismentioning
confidence: 99%
“…[1,8,17] It was also shown that PFAFs can be further derivatized chemically to form donor-acceptor diads and potentially other complex molecular systems. [18,19] The vast majority of PFAF syntheses described in the literature relied on heterogeneous high-temperature reactions between fullerenes and R F · precursors (e.g., R F I or AgOOCCF 3 , see refs. above).…”
Section: Introductionmentioning
confidence: 99%